Branched-Chain Amino Acids as New Biomarkers of Major Depression - A Novel Neurobiology of Mood Disorder - Baranyi, Andreas; Amouzadeh-Ghadikolai, Omid; von Lewinski, Dirk; Rothenhäusler, Hans-Bernd; Theokas, Simon; Robier, Christoph; Mangge, Harald; Reicht, Gerhard; Hlade, Peter; Meinitzer, Andreas (PloS one, 2016)
The proteinogenic branched-chain amino acids (BCAAs) valine, leucine and isoleucine might play an unrecognised crucial role in the development of depression through their activation of the mammalian target of rapamycin (mTor) pathway. The aim of this research project is to evaluate whether BCAAs are altered in patients with major depression and might thus be appropriate biomarkers for major depression. The concentrations of valine, leucine and isoleucine were determined in 71 in-patients with major depression and 48 healthy controls by high-pressure liquid chromatography. Psychiatric and laboratory assessments were obtained at the time of in-patient admittance. The BCAAs are significantly decreased in patients with major depression in comparison with healthy subjects (valine: Mann-Whitney-U: 968.0; p <0.0001, leucine: Mann-Whitney-U: 1246.5; p = 0.013, isoleucine: Mann-Whitney-U: 1252.5; p = 0.014). Furthermore, as shown by Spearman's rank correlation coefficients, there is a significant negative correlation between valine, leucine and isoleucine concentrations and the Hamilton Depression Rating Scale (HAMD-17) as well as Beck Depression Inventory (BDI-II) scores. Our study results are strong evidence that in patients with major depression, BCAAs might be appropriate biomarkers for depression. Reduced activation of the mammalian target of rapamycin (mTor) due to a reduction of BCAAs might play a crucial unrecognised factor in the etiology of depression and may evoke depressive symptomatology and lower energy metabolism in patients with major depression. In the future, mTor and its up- and downstream signalling partners might be important targets for the development of novel antidepressants.